SCHOOL PRINCIPAL LEADERSHIP STYLE IN IMPROVING INSTITUTIONAL QUALITY - Latifah, Nurul; Rizquha, Ach. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Principal Leadership Style in Improving Institutional Quality. The leadership style that exists in an organization has a very important role in achieving organizational success, therefore with a good leadership style, the more likely the organization or institution is to achieve the desired target. The purpose of the research conducted by researchers is to find out and describe how the principal's leadership style improves the quality of the institution and to find out what are the supporting and inhibiting factors of the principal's leadership style.